2012
DOI: 10.1016/j.neuropharm.2010.12.027
|View full text |Cite
|
Sign up to set email alerts
|

DISC1-binding proteins in neural development, signalling and schizophrenia

Abstract: In the decade since Disrupted in Schizophrenia 1 (DISC1) was first identified it has become one of the most convincing risk genes for major mental illness. As a multi-functional scaffold protein, DISC1 has multiple identified protein interaction partners that highlight pathologically relevant molecular pathways with potential for pharmaceutical intervention. Amongst these are proteins involved in neuronal migration (e.g. APP, Dixdc1, LIS1, NDE1, NDEL1), neural progenitor proliferation (GSK3β), neurosignalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(164 citation statements)
references
References 176 publications
(153 reference statements)
2
162
0
Order By: Relevance
“…Consistent with the ability of GIV to modulate several major signaling pathways downstream of both growth factor receptor tyrosine kinases (RTKs) and G protein-coupled receptors (1), we and others have shown that GIV serves as a common modulator of signals during a diverse set of biological processes, e.g. epithelial wound healing, macrophage chemotaxis (3), development (4,5), neuronal migration (6,7), vascular repair (8), autophagy (9), tumor angiogenesis (10), tumor cell migration (3,11), and cancer invasion/metastasis (3,12,13).…”
Section: G␣-interacting Vesicle-associated Protein (Giv) Is a Guaninementioning
confidence: 60%
“…Consistent with the ability of GIV to modulate several major signaling pathways downstream of both growth factor receptor tyrosine kinases (RTKs) and G protein-coupled receptors (1), we and others have shown that GIV serves as a common modulator of signals during a diverse set of biological processes, e.g. epithelial wound healing, macrophage chemotaxis (3), development (4,5), neuronal migration (6,7), vascular repair (8), autophagy (9), tumor angiogenesis (10), tumor cell migration (3,11), and cancer invasion/metastasis (3,12,13).…”
Section: G␣-interacting Vesicle-associated Protein (Giv) Is a Guaninementioning
confidence: 60%
“…Reduced concentrations of other neurotrophic factors (eg, brain-derived neurotrophic factor) have indeed been observed in bipolar disorder (Cunha et al, 2006), supporting a role of neurotrophins in the pathophysiology. Interestingly, APP has also been functionally linked to Disruptedin-Scizhophrenia 1, a risk factor for bipolar disorder and other mental illnesses (Young-Pearse et al, 2010;Bradshaw and Porteous, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…7). DISCUSSION DISC1 is one of only a few single genes definitively associated with psychiatric disease, such as schizophrenia, bipolar disorder and unipolar depression (Bradshaw and Porteous, 2012). However, it is unclear how DISC1 dysfunction results in a series of mental disorders.…”
Section: Disc1 Regulates the Ras/mek/erk Signaling Pathway By Direct mentioning
confidence: 99%